Field observation on thermal environment of an urban street with roadside trees in a tropical climate - Hai, Jian Toh (2015)
This study aims to explore the role of street trees in a tropical city. The outdoor field measurements of roadside trees are carried out at two streets with different tree densities at two major cities, Kuala Lumpur and Petaling Jaya of Malaysia. The results of variation pattern of air and globe temperature are presented. To further analyse the thermal environment, thermal images are captured and mean radiant temperature (MRT) are estimated to compare between all cases.